Innovation systems governance in Bolivia: Lessons for agricultural innovation policies - Hartwich, Frank; Alexaki, Anastasia; Baptista, Rene (International Food Policy Research Institute, 2007)
Traditional approaches to innovation systems policymaking and governance often focus exclusively on the central provision of services, regulations, fiscal measures, and subsidies. This study, however, considers that innovation systems policymaking and governance also has to do with the structures and procedures decision makers set up to provide incentives for innovating agents and the interaction and collaboration among them, thus enabling innovation. Based on the concepts of agent-centered institutionalism and innovation systems, governance can be understood to refer to integrating multiple government and non-government actors in different actor constellations depending on roles, mandates, and strategic visions. Any effort to govern the system composed of those agents needs to take into account the limitations that any policymaking body has in dictating how agents behave and interact. In consequence governance in innovation systems has less to do with executing research and administering extension services and more to do with guiding diverse actors involved in complex innovation processes through the rules and incentives that foster the creation, application, and diffusion of knowledge and technologies. The report presents results from a study that analyzed to what extent the Bolivian Agricultural Technology System (SIBTA), as part of the country’s agricultural innovation system, has complied with a set of governance principles—including participation of stakeholders (especially small farmers) in decision making, transparency and openness, responsiveness and accountability, consensus orientation and coherence, and strategic vision—and compares those principles with benchmarks of innovation systems governance in five other developing countries. Data in Bolivia were collected by means of an expert consultation and interviews with a wide range of key actors and stakeholders from various organizations involved in agricultural innovation in the system. The empirical findings of the study suggest the following: A research and technology transfer program such as SIBTA constitutes only part of an innovation system and there are other important complementary functions with which the government has to comply to foster innovation. Rather than aiming to carry out research and extension, governments should focus on overall planning on the macro level and bringing the above functions together so they reach the innovating agents. To do this they need to involve themselves in planning and policy analysis, the setting of consultation platforms, supporting the building of innovation networks, and setting up specific funding mechanisms. Setting up decentralized semiautonomous agencies that administer funds and design innovation projects does not automatically lead to sufficient participation of local producer organizations and technology providers. More participation requires special rules and incentives to collaborate and the special efforts of all involved, and eventually further decentralization on the regional level. Weak leadership and limited commitment, rather than a decentralized structure or the delegation of too much power, have prevented governments from taking a more active role in governing their innovation systems. Decentralization, however, should not stand in the way of a national strategic vision, and mechanisms need to be put in place to discuss and harmonize national- and local-level priorities. Simply being responsive to the demands of farmers does not necessarily imply that one is generating the best technical solutions. Generating adequate innovations requires the participation of many: leading and other producers, knowledge and technology providers, buyers, input sellers, funding agencies, advisory services, and others. It also requires analysis and identification of technological and market opportunities. Policymakers should foster in-depth analysis of farmers’ demands on the local level through decentralized organizations, which simultaneously help to orient these demands to where technological and market opportunities lie. This requires improved analytical and planning capacities as well as intensive communication with the farmers and agents who benefit from new and promising technologies.